Improving uptake of hepatitis B and hepatitis C testing in South Asian migrants in community and faith settings using educational interventions - a prospective descriptive study. - Kelly, C; Pericleous, M; Ahmed, A; Vandrevala, T; Hendy, J; Shafi, S; Skene, S; Verma, S; Edge, C; Nicholls, M; Gore, C; de Lusignan, S; et al. (Elsevier, 2020)
BACKGROUND: Chronic viral hepatitis (CVH) is a leading contributor to the UK liver disease epidemic, with global migration from high-prevalence areas (e.g. South Asia-SA). Despite international guidance for testing high-risk groups in line with elimination targets, there is no consensus on how to achieve this. OBJECTIVES: (i) Feasibility of recruiting SA migrants to view an educational film on CVH (ii) Effectiveness of the film in promoting testing, knowledge of CVH (iii) Methodological issues relevant to scale-up to randomized trial. METHODS: We recruited SA migrants to view the film (intervention) in community venues (primary care, religious, community), offering dried-blood spot CVH testing immediately afterwards. Pre/post-film questionnaires assessed the interventions effectiveness. RESULTS: Two hundred and nineteen first generation migrants >18yrs (53% female) were recruited to view the film;184 (84%) underwent CVH testing (HBc Ab or HCV Ab positive, demonstrating exposure in 8.5%) at the following sites: n = 112 (51%) religious, n = 98(45%) community, and primary care, n = 9 (4%). Pre (n = 173, 79%) and post (n = 154, 70%) intervention questionnaires were completed. CONCLUSIONS: We demonstrate the feasibility of recruiting first generation migrants to participate in a community-based educational film, promoting CVH testing in this higher-risk group, confirming value of developing interventions to facilitate global WHO plan for targeted case finding, elimination and future randomized controlled trial. We highlight the importance of culturally relevant interventions including faith, and culturally sensitive settings appearing to minimize logistical issues effective at engaging minority groups and allowing ease of access to individuals 'at risk'.